Unwalkable Neighborhoods, Poverty, and the Risk of Diabetes Among Recent Immigrants to Canada Compared With Long-Term Residents - Booth, Gillian L.; Creatore, Maria I.; Moineddin, Rahim; Gozdyra, Peter; Weyman, Jonathan T.; Matheson, Flora I.; Glazier, Richard H. (Diabetes care, 2013)
This study was designed to examine whether residents living in neighborhoods that are less conducive to walking or other physical activities are more likely to develop diabetes and, if so, whether recent immigrants are particularly susceptible to such effects. We conducted a population-based, retrospective cohort study to assess the impact of neighborhood walkability on diabetes incidence among recent immigrants (n = 214,882) relative to long-term residents (n = 1,024,380). Adults aged 30-64 years who were free of diabetes and living in Toronto, Canada, on 31 March 2005 were identified from administrative health databases and followed until 31 March 2010 for the development of diabetes, using a validated algorithm. Neighborhood characteristics, including walkability and income, were derived from the Canadian Census and other sources. Neighborhood walkability was a strong predictor of diabetes incidence independent of age and area income, particularly among recent immigrants (lowest [quintile 1 Q1] vs. highest [quintile 5 Q5] walkability quintile: relative risk [RR] 1.58 [95% CI 1.42-1.75] for men; 1.67 [1.48-1.88] for women) compared with long-term residents (Q1 to Q5) 1.32 [1.26-1.38] for men; 1.24 [1.18-1.31] for women). Coexisting poverty accentuated these effects; diabetes incidence varied threefold between recent immigrants living in low-income/low walkability areas (16.2 per 1,000) and those living in high-income/high walkability areas (5.1 per 1,000). Neighborhood walkability was inversely associated with the development of diabetes in our setting, particularly among recent immigrants living in low-income areas.